ENT300 Donut Marvelous Entreprise / Dayang Norafida Abg Sapini... [et.al] - Abg Sapini, Dayang Norafida; Dollah, Arina Zawiah; Salam, Nur Faezah; Abdillah, Ain Fadilla; Ismail, Khariahtul Shakdah (2011)
The name of our company is Donut Marvelous Enterprise. This business is based on partnership where it consists of five (5) members. The members consist of the Dayang Norafida bt Abg Sapini as General Manager, Arina Zawiah bt Dollah as Administrative Manager, Ain Fadillah bt Abdillah as Operational Manager, Nur Faezah bt Salam as Marketing Manager and Khariahtul Shakdah bt Ismail as Financial Manager. The business initial capital is amounted to RM 14,000 where the contribution of General Manager is RM 10,000 and the others manager contribute RM 7,500 each manager. The loan from Bank Rakyat amounted to RM 24, 625. Lastly, we expect that our business will become more developed in the near future because the demand for donut is high and not many entrepreneur do this business. This will give more advantages for us to make our product more profitable and stabile in the long run.